The Boundaries of Non-Formal Education: The Post-Structuralist Perspective - Garbauskaitė - Jakimovska, Justina (Acta Paedagogica Vilnensia, 2018)
[article in Lithuanian; only abstract and key words in English] In the year 2009, Israeli scientists Shlomo Romi and Marjan Schmida wrote that non-formal education “still suffers from an overemphasis on practice, and lacks a comprehensive, adequate theoretical framework” (Romi, Schmida 2009). The aim of this article is to address the insufficient grounding of non-formal education and to propose a post-structural perspective on it. The article is based on the analysis of literature. The scientific articles, documents and informatikon provided by national and international organizations are interpreted in the frame of post-structural philosophy by using the concepts introduced by Michel Foucault, Gilles Deleuze and Fèlix Guattari. The phenomenon of non-formal education is analyzed as a single concept, without the distinction of nonformal education for children, youth or adults. The stand is that the main principles of non-formal education are universal and transferrable. Therefore, the object of the study is non-formal education, while its aim is to interpret the development of non-formal education in the context of post-structuralism. The following objectives have been set: 1) Describe the main concepts proposed by post-structuralist philosophers; 2) Overview the processes of non-formal education with the main focus on Lithuania; 3) Interpret these processes using the theoretical concepts of post-structuralism. A post-structural perspective on non-formal education helps us unfold the essence and main features of NFE. It can also be useful to explain a common dilemma that is faced by politicians and practicians – non-formal education does not respond to regular practices and it cannot be clearly structured, as new forms are evolving, and old ones are constantly transforming. The post-structural view on non-formal education phenomena is liberating; it helps to distance oneself from the educational documents that only partly reflect the educational reality. The concepts of Foucault, Deleuze and Guattari allow us to see the macropolitical processes while also taking into consideration the micropolitics that create alternatives and innovations.